2011
DOI: 10.3762/bjoc.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Hoveyda–Grubbs type metathesis catalyst immobilized on mesoporous molecular sieves MCM-41 and SBA-15

Abstract: SummaryA commercially available Hoveyda–Grubbs type catalyst (RC303 Zhannan Pharma) was immobilized on mesoporous molecular sieves MCM-41 and on SBA-15 by direct interaction with the sieve wall surface. The immobilized catalysts exhibited high activity and nearly 100% selectivity in several types of alkene metathesis reactions. Ru leaching was found to depend on the substrate and solvent used (the lowest leaching was found for ring-closing metathesis of 1,7-octadiene in cyclohexane – 0.04% of catalyst Ru conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…However,the industrial application of homogeneous olefin metathesis catalysts is hampered bythe expensive catalyst separation processes needed to obtain high-purity chemicals and the contamination of products by Ru catalyst residues that are difficult to eliminate.Therefore, increasing research efforts have been made lately for developing active and stable immobilized supported complexes that allow straightforward catalyst separation and recovery. For example, commercial available Ru-alkylidene complexes immobilized on different supports have been employed without leaching or significant activity loss for olefin metathesis reactions [5,6,7]. Recently, we reported that silicasupported HG complexesare stable, highly active and selective catalysts for the selfmetathesisof methyl oleate [8].…”
Section: -Introductionmentioning
confidence: 98%
“…However,the industrial application of homogeneous olefin metathesis catalysts is hampered bythe expensive catalyst separation processes needed to obtain high-purity chemicals and the contamination of products by Ru catalyst residues that are difficult to eliminate.Therefore, increasing research efforts have been made lately for developing active and stable immobilized supported complexes that allow straightforward catalyst separation and recovery. For example, commercial available Ru-alkylidene complexes immobilized on different supports have been employed without leaching or significant activity loss for olefin metathesis reactions [5,6,7]. Recently, we reported that silicasupported HG complexesare stable, highly active and selective catalysts for the selfmetathesisof methyl oleate [8].…”
Section: -Introductionmentioning
confidence: 98%
“…We presently use Zhan catalyst-1B (Hoveyda-Grubbs type catalyst) to convert 6 to 7 [24] by a ring closure metathesis reaction. This is followed subsequently by cyclopropanation using diethyl zinc in dichloromethane to form protected bicyclic intermediate 10.…”
Section: Chemistrymentioning
confidence: 99%
“…The stability of the catalyst system not only depends on the type of support material and/or the immobilization technique but also on the nature of the solvent as the extent of leaching of active species varies with the solvent type . When Hoveyda‐Grubbs II catalyst (Figure ; Table ) supported on SBA‐15 molecular sieves was employed for metathesis reactions, the highest leaching was observed in dichloromethane while the least was detected in benzene solvent.…”
Section: Metal‐alkylidene Based Heterogeneous Catalyst Systemsmentioning
confidence: 99%